2016
DOI: 10.1080/10717544.2016.1178824
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative pharmaceutical study on colon targeted micro-particles of celecoxib:in-vitro–in-vivoevaluation

Abstract: In order to target celecoxib which is a COX2 inhibitor, with potentials in the prevention and treatment of colitis and colon cancer, it was formulated as microparticles using the solvent/ evaporation method and various pH-dependent Eudragit polymers. The in-vitro evaluation of the prepared microparticles showed spherical and smooth morphology. The encapsulation efficiency and yield were high, indicating that the method used is simple and efficient at this scale. The in-vitro release study showed no release in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Bazan et al developed celecoxib-loaded Eudragit microparticles and carried out in vivo studies in a rat model. They found controlled release of celocoxib (a COX-2 inhibitor, a small molecule drug), and significant decreases in colon inflammation and inflammation markers [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bazan et al developed celecoxib-loaded Eudragit microparticles and carried out in vivo studies in a rat model. They found controlled release of celocoxib (a COX-2 inhibitor, a small molecule drug), and significant decreases in colon inflammation and inflammation markers [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Celecoxib is a class of selective cyclooxygenase 2 (COX-2) inhibitors used for colitis treatment, prevention, and as a chemoprotective agent in adenomatous polyposis-induced colorectal cancer (Arber et al, 2006;Bazan et al, 2016). The COX-2 inhibitor has safety and tolerability in IBD patients but it also has cardiovascular side effects when used for a long time (Miao et al, 2014).…”
Section: Other Celecoxibmentioning
confidence: 99%
“…In vivo assays carried out in a mouse model of colitis showed that the oral administration of this formulation resulted in a better therapeutic activity, compared to other dexamethasone formulations. Bazan et al [52] developed celecoxib-loaded Eudragit microparticles and they carried out in vivo assays in a rat model. Results indicated that the microparticles formulated using Eudragit S100 and, to a lesser extent Eudragit L100-55, provided a controlled release of celocoxib, important reduction of colonic injury, and a decrease of colon inflammation and inflammation markers.…”
Section: Oral Cdds Following the Ph-sensitive Approachmentioning
confidence: 99%